Landscape-Level and Fine-Scale Genetic Structure of the Neotropical Tree Protium spruceanum (Burseraceae) - Fábio de Almeida Vieira; Cristiane Gouvêa Fajardo; Anderson Marcos de Souza; Dulcinéia de Carvalho (International Journal of Forestry Research)
Knowledge of genetic structure at different scales and correlation with the current landscape is fundamental for evaluating the importance of evolutionary processes and identifying conservation units. Here, we used allozyme loci to examine the spatial genetic structure (SGS) of 230 individuals of Protium spruceanum, a native canopy-emergent in five fragments of Brazilian Atlantic forest (1 to 11.8 ha), and four ecological corridors (460 to 1 000 m length). Wright's 𝐹𝑆𝑇 statistic and Mantel tests revealed little evidence of significant genetic structure at the landscape-scale (𝐹𝑆𝑇=0.027; 𝑟𝑀=−0.051, 𝑃=.539). At fine-scale SGS, low levels of relatedness within fragments and corridors (𝑆𝑝=0.008, 𝑃>.05) were observed. Differences in the levels and distribution of the SGS at both spatial scales are discussed in relation to biological and conservation strategies of corridors and forest fragments.